Occupational Blast Wave Exposure During Multiday 0.50 Caliber Rifle Course - Skotak, Maciej; LaValle, Christina; Misistia, Anthony; Egnoto, Michael J.; Chandra, Namas; Kamimori, Gary (Frontiers in Neurology, 2019)
Research on blast overpressure (BOP) experienced by military personnel in operations like breaching, identifies transient, measurable effects on operator readiness. Specifically, blast seems to be associated with suppressed response speed and cognitive function. This work evaluates 50 caliber weapon systems to ascertain BOP effects from the weapon usage. Marksmen were a collection of professionals who use .50 caliber weapon systems as part of their daily activities, and the environment measured was during a training course. The 20 human subjects were equipped with B3 blast gauges and occupational BOP exposure monitored over the course of 3-day training period with measurements taken from 500+ shots. We noted a considerable variation in total cumulative peak pressure (50-350 psi) and impulse (25-180 psi·ms) values. The frequency analysis (number of shots fired by the trainee) revealed that the number of exposures per day varied between 4 to 27 per day (peak at 7: 14.3% of the data), and 2 to 17 per hour (peak at 8: 18% of the data). The cumulative number of exposures was 24-50 per trainee. The neurocognitive performance was evaluated using Defense Automated Neurobehavioral Assessment (DANA) Rapid: Simple Reaction Time (SRT), Procedural Reaction Time (PRT) and Go/No-Go (GNG). The results recorded before the training were a baseline for each training day and compared with the results recorded after and at the end of the day. Only PRT and GNG tests revealed a cumulative increase in proprtion of subejcts with slowed reaction times over the progression of course with concomitant dispersion increase at the end of the day. Noticeably, on average 2/3rd of the trainees performed faster, while 1/3rd of trainees performed these tasks slower, but there was no correlation with the cumulative pressure dosage. The fatigue appears as an aggravating factor affecting the neurocognitive performance, and a more sophisticated evaluation regimen is necessary to discern potential neurological effects. Additional investigation is needed to understand the increasing dispersion of results between subjects and future works should be mindful of such continued trends. Future work should seek to determine the recovery period and longitudinal effects of heavy usage of these weapon systems.